2006
DOI: 10.1111/j.1445-2197.2006.03844.x
|View full text |Cite
|
Sign up to set email alerts
|

Frozen Section for Parotid Surgery: Should It Become Routine?

Abstract: Frozen section in parotid surgery is accurate, inexpensive and may add important information that alters management and improves the outcome. The use of FS routinely in parotid surgery is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
4
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 19 publications
1
36
4
1
Order By: Relevance
“…Contrary to the recommendation by Arabi Mianroodi et al [7] to set a ‘very low' threshold for doing FS in parotid tumor surgery, we found that FS is of limited utility after FNAs consistent with benign disease. This sentiment of setting a low threshold for FS may be secondary to the inclusion of ‘indeterminate salivary gland lesions' in the study.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Contrary to the recommendation by Arabi Mianroodi et al [7] to set a ‘very low' threshold for doing FS in parotid tumor surgery, we found that FS is of limited utility after FNAs consistent with benign disease. This sentiment of setting a low threshold for FS may be secondary to the inclusion of ‘indeterminate salivary gland lesions' in the study.…”
Section: Discussioncontrasting
confidence: 55%
“…Studies such as those done by Schmidt et al [5,8] and Olsen et al [9] have reported the diagnostic accuracy of FS or FNA independently, but the role and value of FS after FNA diagnosis remain unclear. Studies such as those done by Arabi Mianroodi et al [7] report that the threshold for doing FS should be low in order to definitively rule out malignant disease and that FS is indeed cost-beneficial.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Odsetek wyników prawdziwie dodatnich BAC w pracach polskich autorów wahał się od 70% do 75% [11,79]. Na podstawie wyników przedstawionych w literaturze światowej BAC cechuje się czułością od 74% do 85% [1,20,61,117,123]. Pełna zgodność rozpoznania cytologicznego z histopatologicznym w pracy Zbärena i wsp.…”
Section: Zasady Klasyfikacji Klinicznej Raków Duŝych Gruczołów śLinowychunclassified